Aerotoxic syndrome, discussion of possible diagnostic criteria. (3rd May 2020) - Hageman, Gerard; Pal, Teake M.; Nihom, Jik; Mackenzie Ross, Sarah J.; Berg, Martin van den
Abstract: Introduction: The term aerotoxic syndrome (ATS) was proposed 20 years ago to describe a constellation of symptoms reported by pilots and cabin crew following exposure to hydraulic fluids, engine oil, and pyrolysis products during flight. Hydraulic fluids and engine oil contain a large number of potentially toxic chemicals, including various organophosphate compounds (OPCs). However, ATS is not yet recognised as a valid diagnosis in aviation or general medicine, because the incidence and aetiology continues to be debated. Discussion: Early studies report findings from symptom surveys or cognitive assessments of small samples of self-selected aircrew, but objective measures of exposure were lacking. Over the last decade, researchers have used more sophisticated techniques to measure exposure, such as on board monitoring studies and biomarkers of exposure (e.g., reduced levels of serum butyrylcholinesterases [BChE]) and more sophisticated techniques to detect nervous system injuries such as fMRI and autoantibody testing. Consideration has also been given to inter-individual differences in the ability to metabolise certain chemical compounds as a result of genetic polymorphisms and exclusion of other potential causes of ill health. Conclusions: We discuss factors which suggest a diagnosis of probable ATS; recommend an assessment protocol which incorporates the aforementioned techniques; and propose diagnostic criteria for probable ATS, based on our previously reported findings in aircrew and the results of recent studies.